Neurophysiology (EMG): Nail-patella syndrome: a rare etiology of inherited peripheral neuropathy?. (3rd June 2015) - Shafi, S; Bourque, P
Abstract : Background: Nail-patella syndrome (NPS) is an inherited autosomal dominant disease, with an incidence of approximately 1 in 50, 000. It ischaracterized by nail dysplasia, hypoplastic patellae, other bone deformities and open angle glaucoma. The phenotype is variable. Methods: Case report Results: A 66 year old male presented with complaints of mild loss of sensation in both feet with gradual proximal spread to his knees over the past decade. There was no history of pain, paresthesias, autonomic dysfunction or weakness. Examination showed pectus excavatum with symmetrically dystrophic fingernails. Sensation to crude touch, pain and temperature were reduced up to mid shin, and vibration sense was diminished till the malleoli symmetrically. Electrophysiologic studies revealed a mild to moderate length-dependent polyneuropathy of axonal type. Detailed blood screening studies were negative. Genetic testing revealed the diagnosis of nail-patella syndrome with LMX1B gene mutation on chromosome 9q34. The lack of an identifiable acquired cause and the symmetric, slowly progressive and "painless" nature of the patient's peripheral neuropathy point toward an inherited etiology. Conclusion: We present a case of slowly progressive sensorimotor axonal polyneuropathy in a patient with a diagnosis of NPS, which has not been previously reported. Peripheral nervous system disorder may be a variable phenotypic manifestation of LMX1B gene mutation.